The energy cost of walking and running with taped vs. untapped ankles using adhesive inelastic tape - Giannopoulos, G.; Tripolitsioti, A.; Papachristoforou, C.; Papadopoulos, A. (Biology of Exercise, 2010)
To determine the difference in the energy cost of walking and running with taped ankles vs. untapped ankles, twelve male subjects (all non athletes) ranging from 24 - 28 yrs of age, had their Oxygen uptake (VO2) measured while walking and running on the treadmill. They had their ankles taped with inelastic adhesive tape, walked on the treadmill at the speed of 5 km / hr, and at running speed of 10 km / hr. An ankle arthrometer was used to quantify anteroposterior (AP) translation and frontal plane inversion-eversion (I - E) tilt of the talocrural - subtalar joints under untapped and taped conditions in participants. The trials for walking and running were repeated at the same speed without the ankles taped. The VO2 values with the ankles taped while walking and running were statistically significant (p = 0.05) compared to the VO2 values of walking and running without the tape. These results indicate that the energy requirement for walking and running while the ankles are taped with the inelastic tape was higher compared to the same type of work performed, for the same duration while the ankles were not under the influence of the tape. A large portion of this increase may be attributed to the taping procedure and the adhesiveness of the tape. In addition, the increased energy cost of locomotion with the ankles taped appears to place a limiting stress to the untrained non athletic subjects.